Viewing mathematics teachers’ professional identity in the Kingdom of Saudi Arabia through the Lens of Social Theory of Learning and Gender Schema Theory - Abdullah, AlghamdiHamad (2021)
The purpose of the study is to explore the profile of the professional identity of Mathematics teachers in the Kingdom of Saudi Arabia under the influence of Social Theory of Learning and Gender Schema Theory. The descriptive approach is used in this study. The sample size of this study is 600 secondary Mathematics teachers. This study used an adapted version of the questionnaire designed by Albaqi'i (2014) to profile the Mathematics Teachers' Professional Identity (TPI) of the participants. The findings of the study showed that there is no significant difference of Mathematics TPI in gender wise, but there is significant differences of Mathematics TPI based on teaching experiences and qualifications among the Mathematics teachers in Kingdom of Saudi Arabia.The finding of the profile analysis gives some implications to understand how TPI is evolved among Mathematics teachers in the Kingdom of Saudi Arabia through the influences of teaching experience and professional development, which represent by their qualifications. The findings also informed that male and female Mathematics teachers did not perceive their professional identity differently, which suggest that Saudi Arabia culture permit equal participation in building their professional identity.